Investigating the Role of Environmental Costs in Supporting Supply Chain to Build Competitive Advantage - Abdulwahab Razzaq Alwan AL-yasar; Zainab Hadi Mahdi; Jasim Idan Barrak (International Journal of Supply Chain Management, 2019)
Each organization requires three important sources of human resources, financial resources and natural resources to carry out its activities. Given the importance of environmental costs, they can be considered as part of the cost of products or services of business units. The purpose of this paper is to examine the role of environmental costs in supporting supply chain to build competitive advantage. The results of the survey showed that reporting environmental costs could have many benefits for companies because this makes it possible for companies to do their best to do their best and increase their credibility with customers and the entire community. In this way, the calculation of environmental costs plays a role in supply chain to build competitive advantage for companies.